The Effect of using Zoom Application on Students Speaking Skills - Jesika; Rona Elfiza; Gatot Subroto (English Language Education Study Program Universitas Maritim Raja Ali Haji, 2022)
This study intended to see whether there is an effect of using the zoom application on student’s speaking skills or not. This study was conducted at SMP Negeri 11 Tanjungpinang in the academic year of 2021/2022. The authors selected class VIII.4 which the number of students was 31 as the object of this study. The authors used quantitative methodology and the design was a pre-experimental design in which the authors used one-group pre-test/post-test with treatment. In this study, the authors used an oral test as the instrument of this study. The alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. It could be seen from data calculated using paired sample t-test formula. Based on the data calculated, it could be seen that the significance was 0.133. It was normal because 0.133 > 0.005. While the Sig. 2 tailed was 0.000. It means that there is a significant effect of using zoom application on student’s speaking skills at 8th grade of SMP Negeri 11 Tanjungpinang because the sig.2 tailed 0.000< 0.005. Based on the findings, the authors suggest the teacher use zoom application for teaching speaking, because this application gave a significant effect on student’s speaking skills.